Cost-effectiveness analysis of personalised versus standard dosimetry for selective internal radiation therapy with TheraSphere in patients with hepatocellular carcinoma - Carla Rognoni; Maria Rosa Barcellona; Irene Bargellini; Maria Grazia Bavetta; Marilena Bellò; Maurizia Brunetto; Patrizia Carucci; Roberto Cioni; Laura Crocetti; Fabio D’Amato; Mario D’Amico; Simona Deagostini; et al. (Frontiers in Oncology, 2022)
AimsTo perform a cost-effectiveness analysis (CEA) comparing personalised dosimetry with standard dosimetry in the context of selective internal radiation therapy (SIRT) with TheraSphere for the management of adult patients with locally advanced hepatocellular carcinoma (HCC) from the Italian Healthcare Service perspective.Materials and methodsA partition survival model was developed to project costs and the quality-adjusted life years (QALYs) over a lifetime horizon. Clinical inputs were retrieved from a published randomised controlled trial. Health resource utilisation inputs were extracted from the questionnaires administered to clinicians in three oncology centres in Italy, respectively. Cost parameters were based on Italian official tariffs.ResultsOver a lifetime horizon, the model estimated the average QALYs of 1.292 and 0.578, respectively, for patients undergoing personalised and standard dosimetry approaches. The estimated mean costs per patient were €23,487 and €19,877, respectively. The incremental cost-utility ratio (ICUR) of personalised versus standard dosimetry approaches was €5,056/QALY.ConclusionsPersonalised dosimetry may be considered a cost-effective option compared to standard dosimetry for patients undergoing SIRT for HCC in Italy. These findings provide evidence for clinicians and payers on the value of personalised dosimetry as a treatment option for patients with HCC.